2021
DOI: 10.1021/acsaem.1c01313
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Coexsolution of Metal Nanoparticle-Decorated Double Perovskites As Anode Materials for Solid Oxide Fuel Cells

Abstract: Because of the excellent catalytic activity of nanoparticles, their in situ exsolution on perovskite surfaces has received extensive attention in the field of catalysis. Herein, a unique A- and B-site coexsolved double perovskite, SrBiFeTiO6−δ (SBFT), is used as an anode material in a solid oxide fuel cell (SOFC). A study of its crystal structure confirmed that the cubic structure of the SBFT perovskite has reasonable structural stability under a hydrogen (H2) atmosphere, even though metallic Bi and Fe exsolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 50 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…Ru (6 occurrences), Ag (4), Cu (3), and Re (2) only appear in few publications. Nanoparticles comprised of the following are mentioned once each: Au, 100 Bi, 70 Ir, 101 Mo, 58 Rh, 102 (PrBa)O x , 103 and SrO. 104…”
Section: Overview Of Published Workmentioning
confidence: 99%
“…Ru (6 occurrences), Ag (4), Cu (3), and Re (2) only appear in few publications. Nanoparticles comprised of the following are mentioned once each: Au, 100 Bi, 70 Ir, 101 Mo, 58 Rh, 102 (PrBa)O x , 103 and SrO. 104…”
Section: Overview Of Published Workmentioning
confidence: 99%
“…Previous studies have shown that the addition of bismuth as a dopant has the potential to improve the performance of the electrode. [ 19–29 ] The B‐ordered Ba 2 Bi x Sc 0.2 Co 1.7 O 6− δ (BBSC) double perovskite cathode material was reported by Li et al., [ 22 ] and neutron diffraction analysis confirmed that the co‐doping of Bi and Sc enhanced the B─O─B' interaction, thereby promoting the migration of oxygen ions and increasing their conductivity. Zou et al.…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies have shown that the addition of bismuth as a dopant has the potential to improve the performance of the electrode. [19][20][21][22][23][24][25][26][27][28][29] The B-ordered Ba 2 Bi x Sc 0.2 Co 1.7 O 6−𝛿 (BBSC) double perovskite cathode material was reported by Li et al, [22] and neutron diffraction analysis confirmed that the co-doping of Bi and Sc enhanced the B─O─B' interaction, thereby promoting the migration of oxygen ions and increasing their conductivity. Zou et al [23] reported the utilization of Ca 3−x Bi x Co 4 O 9+𝛿 (0 < x ≤ 0.5) as the cathode material for SOFCs, demonstrating excellent thermal compatibility and stability when combined with Ce 0.8 Sm 0.2 O 1.9 electrolyte.…”
Section: Introductionmentioning
confidence: 99%